1994
DOI: 10.1007/bf01739206
|View full text |Cite
|
Sign up to set email alerts
|

Can antitakeover activity really create wealth? Evidence from Australia

Abstract: This paper examines management-induced antitakeover activity which occurred in

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2000
2000
2018
2018

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 19 publications
1
6
0
Order By: Relevance
“…It may be that the elimination of some relevant nominee shareholders when measuring the extent of institutional holdings may have produced this unexpected result. 30 However, the insignificance of institutional holdings is consistent with the findings of Armstrong, Lange and Woo (1994), with respect to ATCA proposals. 31…”
Section: The Role Of Shareholderssupporting
confidence: 90%
See 4 more Smart Citations
“…It may be that the elimination of some relevant nominee shareholders when measuring the extent of institutional holdings may have produced this unexpected result. 30 However, the insignificance of institutional holdings is consistent with the findings of Armstrong, Lange and Woo (1994), with respect to ATCA proposals. 31…”
Section: The Role Of Shareholderssupporting
confidence: 90%
“…19. This was examined by Armstrong, Lange and Woo (1994), who found that the majority of anti-takeover amendments occurred subsequent to the amendment of the Companies (Acquisition of Shares) Act in June 1986. North Broken Hill Holdings was the only company to propose partial takeover restrictions prior to 24 June 1986, and was able to do this as the uncertainty surrounding the revisions to the corporations legislation had been largely resolved by this time.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations